Anaphylaxis: knowledge among oral and maxillofacial surgeons - Vasconcelos, Amanda Freire de Melo (2020)
The aim of the present study was to evaluate knowledge regarding the conduct and adequate management of anaphylaxis on the part of oral-maxillofacial surgeons. A quantitative evaluation was performed through a cognitive survey on the subject. The sample was composed of 104 specialists and who participated in the Brazilian Oral-Maxillofacial Surgery and Traumatology Conference. A total of 31.7% of the interviewees were unaware of any protocol for anaphylaxis. Among those with information on the subject, the majority (78.8%) reported that adrenaline is the main drug for the treatment of anaphylaxis, but 50% of these individuals did not know the correct dosage and only 35.6% reported that intramuscular administration was the proper route. Only 12.5% reported having witnessed a case of anaphylaxis and all such cases were resolved with a favorable outcome. A considerable number of surgeons (34.6%) reported not having any drug for emergency care in their offices, but the majority (71.2%) reported being capable of administering such drugs. The present findings revealed a lack of knowledge on the part of many oral-maxillofacial surgeons regarding anaphylactic reactions and treatment.